Retropharyngeal Abscess Masquerading As Mumps In A 7-Month-Old: A Rare Case Report - S. Shetti, Preeti; Gupta, Ishwari; Goel, Divit (Journal of Neonatal Surgery, 2025)
Aim: To present a rare but potentially life-threatening case of retropharyngeal abscess (RPA) in an infant with mumps, highlighting the critical role of early recognition, appropriate imaging, and prompt surgical management in preventing airway compromise. Background: Mumps is a contagious viral illness primarily seen in children, often characterised by swelling of the parotid glands. While generally self-limiting, it can occasionally result in serious complications. One such uncommon but severe complication is a retropharyngeal abscess—an infection in the deep neck space that can lead to significant morbidity due to airway obstruction. In infants, this diagnosis is particularly challenging, making early detection vital to avoid fatal outcomes. Case Description: A 7-month-old infant was brought in with a 10-day history of high fever, difficulty feeding, excessive drooling, noisy breathing, and neck stiffness. Despite receiving antibiotic treatment elsewhere, there was no improvement, necessitating referral to a higher centre. Upon evaluation, the child was started on broad-spectrum antibiotics, and radiological imaging revealed a retropharyngeal abscess on the right side. Given the impending risk of airway compromise, an emergency transoral incision and drainage procedure was performed. The child responded well to the intervention and completed recovery without complications, subsequently being discharged in stable condition. Conclusion: This case underscores the necessity for timely identification and intervention in infants with suspected RPA, especially when secondary to infections like mumps. Imaging studies are essential for accurate diagnosis, while a combination of broad-spectrum antibiotics and surgical drainage forms the cornerstone of effective management. Maintaining a high index of suspicion in children presenting with upper airway symptoms can significantly reduce the risk of serious complications.